Adult Vallecular Vascular Malformation - A Case Report - Thakur, Pooja; Kumar, Amit; Sood, Rachit; Prasath, Ramesh; Yadav, Akhilesh Chandra; Ravichandran, Nivedhan (Asian Journal of Medical Research, 2022)
Vascular malformations are one of the most common forms of congenital benign lesions. The majority of them arise in the head & neck region and they are rare in adults. Laryngeal vascular malformations mostly involve supraglottis and glottis. We are reporting this case of vascular malformation, involving vallecula, a rare site reported in the literature.